The comparison of postural balance level between advanced sport climbers and sedentary adults - Aras, D.; Kitano, K.; Phipps, A. M.; Enyart, M. R.; Akça, F. A.; Koceja, D. M.; Ewert, A. W. (International Journal of Applied Exercise Physiology, 2018)
Besides being an important factor in preventing musculoskeletal injuries in daily life, the sport of rock climbing affects balance as well. Hence, the purpose of the study was to compare the postural balance level between experienced sport climbers and sedentary adults. A total of 10 advanced sport climbers and 10 sedentary adults participated in the study. All subjects performed three balance tasks on a force platform with the eyes open, eyes closed, and during a visual conflict condition. All testing was performed with hands on hips and while barefoot. Subjects were instructed to stand quietly on the force plate for 90-second trials. The ranges, and SDs (standard deviation) of sway in the medio-lateral (ML) and anterior-posterior (AP) axes, and the sway path values [on the ML and AP axes and the general sway (mm)] were recorded. Although climbers had superior scores in all of the balance values, only significant differences were found in the Range-ML with the eyes open condition, and in Range-AP and in SD-AP with the eyes closed. Intragroup analyses showed that both groups had statistically higher scores in Range-AP, SD-AP, Sway path, and Sway path-AP values with the eyes closed condition, and only climbers in Range-ML, and only sedentary group in Sway path-ML again with the eyes closed condition. In accordance with the results it can be concluded that advanced level sport climbers produces significant advantages in the postural balance level. Therefore, sport climbing could be evaluated as a type of physical activity to enhance the balance level.